Modul komputasi matematika untuk meningkatkan motivasi mahasiswa - Arigiyati, Tri Astuti; Sulistyowati, Fitria; Kusmanto, Kusmanto; Kusmanto, Benidectus (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2020)
This study aims to develop a mathematics computation learning module using the Matlab program. Matlab is a computer program that is used to solve various math problems. This study uses a simplified Borg and Gall development model with the following stages: (1) product analysis; (2) initial product development; (3) Expert validation and product revision; (4) limited field trials and product revisions; (5) main field trials and final products. The first three stages have been carried out in the previous year and produced a valid Mathematical Computing module. In the limited field trial, it was found that the student response to the Mathematics Computing module was categorized as good with an average score of 3.86, while in the main trial an average score was 3.98 which was categorized good for the 6 aspects assessed. Based on these results it can be concluded that this module is suitable for use in learning mathematics computation. This module is expected to motivate students to learn Mathematical Computing so that learning objectives can be achieved.